Analisis Kesulitan Menulis Permulaan pada Mata Pembelajaran Bahasa Indonesia Siswa Kelas II di SD Negeri Samir Tulungagung - Khoirun Alfizein Khasanah; Rahyu Setiani (Universitas Nusantara PGRI Kediri, 2024)
This study aims to describe and analyze the difficulties in writing the beginning of the Indonesian language course for second-grade students at Samir State Elementary School. The research method used is descriptive qualitative. The instruments used are observation sheets, interview sheets for 3 students and second-grade teachers, and documentation. The results of the study on the difficulties in writing the beginning of the Indonesian language course for second-grade students at Samir State Elementary School, students (MRS, KAA, HPN) have not met the eleven indicators of difficulties in writing the beginning because they often play with their friends during learning, tease their friends, have difficulty remembering the letters to be written, their writing is mixed up, often reduce words and often add words, have difficulty writing uppercase and lowercase letters. The form of compact cooperation and giving serious attention between teachers and parents in guiding students can certainly produce good and more optimal results.